Price duration with two-sided pricing rules - Carlson, John; Buckle, Robert (School of Management Working Papers, 1995)
Substantial evidence exists that some firms are lowering prices while other firms are raising prices, even in highly inflationary times. A stochastic process with disparate shocks to individual firms’ cost and demand accommodates this phenomenon within the menu cost framework. A Markov chain representation of this process can be related directly to the classical ruin problem in probability theory. If firms follow the optimal price-resetting rules, there is a mapping from data to parameters of the Markov process. Data from a variety of industries in the USA and New Zealand reveal that lower inflation increases the time between price changes whether the changes are up or down and that price duration was less sensitive to a decline in inflation rates in New Zealand than in the USA.